Answer:
68
Step-by-step explanation:
The expression is given as:
4( 3+ 7y) + 6(2 - y)
It is known that y is equal to 2. Therefore, substitute 2 in for y.
4(3+7(2))+6(2-2)
Now, solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction
Solve inside of the parentheses first.
4(3+7(2))+6(2-2)
4(3+14)+6(0)
4(17)+6(0)
Multiply
68+0
Add
68
I believe it would be (-2,-2) i may be wrong though i dont have my graphing papers
Answer:
a14 = -40,960
Step-by-step explanation:
The sequence has a first term of 5 and a common ratio of -10/5 = -2, so the n-th term is given by ...
an = a1·r^(n-1)
an = 5·(-2)^(n-1)
The 14th term is then ...
a14 = 5·(-2)^(14-1) = -5·2^13 = -5·8192
a14 = -40,960